Performances and Skills of Cotabato City’s Mathematics Pre-service Teachers in Problem Solving - Mobarac R. Dimasindel (Southeast Asian Mathematics Education Journal, 2017)
The performances in problem solving of mathematics pre-service teachers in Cotabato City was determined in this study using qualitative research design. The Polya’s theory (1954) on problem solving skills in terms of understanding the problem, devising a plan, carrying out the plan, and looking back was used in classifying and describing the performances of the respondents in the conducted problem solving skill test. Ten (10) mathematics preservice teachers from Cotabato City State Polytechnic College enrolled for the school year 2014-2015 were chosen as respondents using purposive sampling. The study then found out that the respondents’ level of proficiency in problem solving in terms of understanding the problem, devising a plan, and looking back is ‘Developing’ as they cannot define the problems adequately and cannot follow them to conclusion. However, they are at the level of ‘Approaching Proficiency’ in terms of carrying out the plan.